POLA PENGELUARAN PANGAN RUMAH TANGGA PETERNAK IKAN LELE DI KOTA PEKANBARU - Elinur Elinur; Heriyanto Heriyanto (Indonesian Journal of Agricultural Economics, 2021)
The pattern of food consumption is a description of the combination of food choices that will be consumed by households to meet basic needs and adequate and balanced nutritional intake. This study aims to analyze the characteristics of catfish farmers, the structure of income and household expenditure and the factors that influence the pattern of food expenditure. This study has used a survey method where was located in Pekanbaru City. This study used cross section data obtained by interview method. The sampling method used simple random sampling with 98 catfish farmers. Data analysis used descriptive and inferential statistical analysis with binomial linear regression. There are four findings from this study, among other: First, catfish farmer has a productive age and have SMA education. The number of family members is 5 people. Experience raising catfish for 6-7 years. Second, household income consists of income on farming of catfish, income off farming of catfish and nonfarming income. Income on farming of catfish has the largest contribution in the structure of household income. Third, household expenditures consist of food and non-food expenditures. Food expenditure has the largest proportion relative to non-food expenditure. Fourth, the dominant factors that influence the pattern of household food expenditure of catfish farmers are income on farming of catfish, education of the farmer's wife and household savings, while income off farming of catfish, the number of family members and household assets do not significantly affect the pattern of household expenditure.